Danggui-Shaoyao-San Promotes Amyloid-β Clearance through Regulating Microglia Polarization via Trem2 in BV2 Cells - Gongcan Chen; Mengmeng Han; Yi Chen; Yaling Lei; Min Li; Li Wang; Chen Wang; Yangxue Hu; Jinghu Niu; Cong Yang; Yousheng Mo; Qi Wang; et al. (Journal of Integrative Neuroscience, 2023)
Background: Alzheimer’s disease (AD) is a chronic neurodegenerative brain disorder currently without satisfactory therapeutic treatments. Triggering receptors expressed on a myeloid cells-2 (Trem2) gene mutation has been reported as a powerful AD risk factor that induces Trem2 gene deletion aggravated microglia disfunction and Amyloid-β (Aβ) aggregation in the brain. The traditional Chinese medicine (TCM) formula Danggui-Shaoyao-San (DSS) has shown therapeutic effect on alleviating the symptoms of AD. However, the neuroprotective effect and underlying mechanism of DSS against AD is still far from fully understood. Methods: Double-label immunofluorescence and Western blotting were employed to evaluate the different polarization states of mouse BV2 microglial (BV2) cells after lipopolysaccharide (LPS) or interleukin (IL)-4 treatment. Trem2 over-expression lentiviral vector and Trem2 siRNA were used respectively to evaluate the effect of Trem2 on microglia polarization via detecting the proteins expression of iNOS and arginase1 (Arg1) by Western blotting while the Aβ-scavenging capacity of BV2 cells was assessed by flow cytometry. Cell counting kit-8 (CCK8) assay was performed to assess the effect of DSS on the viability of BV2 cells. Flow cytometry was used to investigate the effect of DSS on the Aβ-scavenging capacity of BV2 cells treated with corresponding concentration of DSS-containing serum. Protein of Trem2 and the gene expression of the M1 or M2 phenotype in BV2 cells treated with DSS after Trem2 over-expression or silence were detected by Western blot and RT-qPCR, respectively. Results: In vitro experiments. DSS exhibited anti-inflammatory and neuroprotective functions. It was found that Trem2 had an effect on inducing a shift of M1 microglia towards the M2 phenotype and enhanced the Aβ-scavenging capacity of BV2 cells, further that DSS administration relieved inflammation by engulfing Aβ through the activities of Trem2. Importantly, DSS treatment effectively increased the Aβ-scavenging capacity of BV2 cells through accelerating the shift of M1 microglia towards an M2 phenotype via increasing Trem2 expression. Conclusions: Results demonstrated that DSS promoted the clearance of Aβ through the regulation of microglia polarization via increased expression of Trem2 in BV2 cells.